PERAN KONEKSI POLITIK, KERAGAMAN GENDER, KINERJA KEUANGAN, DAN INTENSITAS ASET TETAP DALAM MENDORONG AGRESIVITAS PAJAK PERUSAHAAN - Etha Nor Cahyanti; Nita Andriyani Budiman; Ulva Rizky Mulyani (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Tax aggressiveness is an activity carried out with the main objective of reducing the company’s tax burden. This study aims to analyze the effect of political connections, gender diversity, financial performance, and fixed asset intensity on tax aggressiveness. The population in this study were sector consumer non cyclical companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. Sampling in this study used a purposive sampling technique with a total sample 184. This study uses a panel data regression analysis method using the Eviews version 12 analysis tool. The results of this study indicate that fixed asset intensity has a positive effect on tax aggressiveness, and financial performance has a negative effect on tax aggressiveness, while political connections and gender diversity have no effect on tax aggressiveness.